Lateral Meniscus Allograft Transplant With Capsulodesis and an Osteochondral Allograft to the Lateral Femoral Condyle - Jose Rafael Garcia BS; Felicitas Allende MD; Jorge Chahla MD, PhD (SAGE Publishing, 2024)
Background: Anterior cruciate ligament (ACL) injuries frequently present with lateral meniscal injuries, and when irreparable, this may lead to meniscectomy, increasing the risk for osteoarthritis. Lateral meniscal allograft transplant (LMAT) can restore knee function and proper contact pressures. When combined with osteochondral allograft (OCA) for chondral defects, results are highly positive. Indications: LMAT is indicated in relatively young patients (<50 years of age) with a symptomatic, meniscus-deficient knee that has failed conservative treatment. The knee must be stable, without articular cartilage damage that cannot be repaired, and patients should be able to adhere to postoperative rehabilitation and future care. Indications for OCA include young, active patients with posttraumatic osteochondral defects, osteonecrosis, osteochondritis dissecans, large focal defects, previous cartilage repair failure, or patellofemoral joint cartilage lesions. Technique Description: After a diagnostic arthroscopy is performed and concomitant injuries are ruled out, the lateral meniscal tissue is debrided to a 1- to 2-mm rim for the recipient site preparation. Tibial sockets for root fixation are created using tibial guides and passing sutures are placed. A capsulodesis is performed to reduce meniscal extrusion by securing the lateral capsule through a transtibial tunnel to the anteromedial tibial cortex with high-strength sutures. A meniscal allograft, prepared with bone plugs, is introduced through an enlarged anterolateral portal. After it is accurately positioned, it is stabilized using Fast-Fix Flex devices and circumferential sutures. The bone plug sutures are then fixed through the tibial tunnels to the anteromedial tibial cortex with a button. The large cartilage defect is addressed with an OCA transplant, involving defect measurement, careful reaming, and press-fit insertion of a donor plug, ensuring congruent articulation. Results: Patients can expect improved clinical outcomes and high patient satisfaction with LMAT and concomitant OCA. The use of bone plugs minimizes soft tissue dissection while achieving solid osseous fixation. Discussion/Conclusions: LMAT with OCA leads to restored contact pressures to near-physiological levels, a high patient satisfaction of over 85%, and mean allograft survival of 16 years. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.